2003
DOI: 10.1007/s00464-002-8738-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic and open gastrectomy for malignant disease

Abstract: Laparoscopic gastrectomy for malignancy is a viable alternative to open surgery. Laparoscopic techniques can obtain adequate margins and follow oncologic principles. Short-term follow-up evaluation shows no difference in survival rates between the two approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 14 publications
4
49
3
Order By: Relevance
“…Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies. 16,17,33 However, we found no difference in length of stay. We performed a laparoscopic assisted technique that included a limited median incision for digestive reconstruction.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies. 16,17,33 However, we found no difference in length of stay. We performed a laparoscopic assisted technique that included a limited median incision for digestive reconstruction.…”
Section: Discussioncontrasting
confidence: 68%
“…Comparative studies consisted of retrospective designs, 14,15,26-32 2 case-matched cohorts 17,33 and a single prospective randomized controlled trial (RCT) by Huscher and colleagues. 16 Sample sizes were limited owing to the Western gastric cancer reality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…The major complications are bleeding, gastric stasis, anastomosis leakage, and wound infection [4]. In the published literature, the incidence of postoperative complications with LAG ranges from 5.4% to 23.3% [5][6][7][8][9][10][11]. However, fewer than 50 patients participated in these studies.…”
mentioning
confidence: 99%